2018
DOI: 10.2503/hortj.okd-150
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Blossom-end Rot Resistance in Tomato Cultivars is Associated with Total Ascorbate rather than Calcium Concentration in the Distal End Part of Fruits <i>per se</i>

Abstract: Calcium is widely accepted as the main factor responsible for blossom-end rot (BER) appearance in tomato (Solanum lycopersicum L.) fruit. However, reactive oxygen species (ROS), which can damage plant tissues have also been proposed to initiate BER appearance in tomatoes and other fruit-bearing vegetables. Ascorbate, the major antioxidant in tomato fruit, is generally lower during green fruit development, which corresponds to the stage of BER appearance. Accordingly, one hypothesis is that tomato cultivars wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
0
13
2
1
Order By: Relevance
“…It is possible that the 19 spray applications of Ca-EDTA, both with and without Si, did not result in an increase in Ca accumulation in the shoots and fruits ( Fig. 2E, F) due to the low concentration that we used in the present experiment (1 g L -1 or 25 mM of Ca-EDTA) compared to the recommended, that is, 1.8 g L -1 or 45 mM Ca (Ho and White, 2005) With respect to the non-occurrence of BER in our experiment, although other authors have found BER in the MT cultivar (Gaion et al, 2019), it was found that tomatoes with this disorder at the beginning of development had a distribution and concentration of Ca similar to normal fruits, suggesting that Ca deficiency may not be the primary and exclusive cause of apical rot in tomatoes (Nonami et al, 1995;Rached et al, 2018).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…It is possible that the 19 spray applications of Ca-EDTA, both with and without Si, did not result in an increase in Ca accumulation in the shoots and fruits ( Fig. 2E, F) due to the low concentration that we used in the present experiment (1 g L -1 or 25 mM of Ca-EDTA) compared to the recommended, that is, 1.8 g L -1 or 45 mM Ca (Ho and White, 2005) With respect to the non-occurrence of BER in our experiment, although other authors have found BER in the MT cultivar (Gaion et al, 2019), it was found that tomatoes with this disorder at the beginning of development had a distribution and concentration of Ca similar to normal fruits, suggesting that Ca deficiency may not be the primary and exclusive cause of apical rot in tomatoes (Nonami et al, 1995;Rached et al, 2018).…”
Section: Discussioncontrasting
confidence: 66%
“…With respect to the non‐occurrence of BER in our experiment, although other authors have found BER in the MT cultivar ( Gaion et al, 2019), it was found that tomatoes with this disorder at the beginning of development had a distribution and concentration of Ca similar to normal fruits, suggesting that Ca deficiency may not be the primary and exclusive cause of apical rot in tomatoes ( Nonami et al, 1995; Rached et al, 2018).…”
Section: Discussioncontrasting
confidence: 61%
“…In future studies, it is important to determine localized cellular calcium deficiency by investigating subcellular [Ca 2+ ] partitioning in fruit sections (de Freitas et al, 2011). Furthermore, the lack of a direct link between [Ca 2+ ] deficiency and the BER incidence in several studies also suggests a role for antioxidant levels in the distal part of the fruit in the development of BER symptoms (Hagassou et al, 2019;Nonami et al, 1995;Rached et al, 2018;Saure, 2001).…”
Section: Sectionmentioning
confidence: 99%
“…Even though a central role for Ca 2+ in the development of BER has been postulated for many years, neither a consistent solution nor a direct link to fruit Ca 2+ concentration has been conclusively demonstrated (Ho and White 2005 ). Therefore, other physiological links to the causes of BER such as reactive oxygen species (ROS) formation have recently gained prominence (Rached et al 2018 ). Because of its destructive activity, excessive ROS release upon exposure of plants to stress conditions causes cell membrane lipid peroxidation, membrane leakage, and subsequently cell death, which can lead to the development of BER (Aktas et al 2003 ; Rached et al 2018 ; Van Breusegem and Dat 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, other physiological links to the causes of BER such as reactive oxygen species (ROS) formation have recently gained prominence (Rached et al 2018 ). Because of its destructive activity, excessive ROS release upon exposure of plants to stress conditions causes cell membrane lipid peroxidation, membrane leakage, and subsequently cell death, which can lead to the development of BER (Aktas et al 2003 ; Rached et al 2018 ; Van Breusegem and Dat 2006 ). Moreover, ROS production reaches a maximum, when the rate of cell expansion during fruit growth is at its maximum (Aktas et al 2003 ).…”
Section: Introductionmentioning
confidence: 99%